Relationship between customer, cost, convenience, and communication on consumer buying decisions - Eko Agus Susilo; Shofia Rizky Khoirunnisa; Wahyu Wiyani (Jurnal Penelitian, 2022)
The purpose of this study was to determine whether the customer is positively related to the buying decisions of consumers at Cafe Bukit Delight Malang, to determine whether the cost is positively associated with the buying decisions of consumers to Cafe Bukit Delight Malang, to determine whether convenience is positively related to the buying decisions of the consumer to Cafe Bukit Delight Malang, and to find out whether the communication is positively associated with the buying decisions of the consumer to Cafe Bukit Delight Malang.Â  The benefit of this research is that it becomes material for consideration, input for companies, and insights for future researchers. The results of this study can be concluded that the variables customer, cost, convenience, and communication have a significant and direct relationship with consumer buying decisions.Â  The results of this study indicate that the dominant influencing variable is communication.